Efficient aqueous hydrodeoxygenation of vanillin over a mesoporous carbon nitride-modified Pd nanocatalyst. Issue 73 (20th July 2016) - Jiang, Hezhan; Yu, Xiaolong; Peng, Xiaolun; Zhang, Haifu; Nie, Renfeng; Lu, Xinhuan; Zhou, Dan; Xia, Qinghua
Abstract : CN is prepared via polymerization between EDA and CF, which renders coordinated Pd with high activity for selective HDO of vanillin at low H2 pressure and temperature. This Pd/CN is reusable and the best TOF reaches 295.4 h −1 . Abstract : Highly mesoporous carbon nitrides (CN) are synthesized through a simple polymerization reaction, including ethylenediamine (EDA), organic chlorides, with nano SiO2 as a hard-template. The degree of polymerization of the as-synthesized CN can easily be controlled by varying the organic chlorides. The CN derived from chloroform exhibits a low degree of polymerization, along with a high specific surface area of 315.9 m 2 g −1 and pore volume of 0.87 cm 3 g −1, in which the mesopore volume proportion reaches as high as 90.9%. Owing to the rich N groups (15.6 wt%), this basic network with open channels renders homogeneously dispersed Pd coordinated in the mesoporous carbonaceous framework and creates a highly active and stable Pd/CN catalyst for the selective hydrodeoxygenation of vanillin at low pressure (<1 MPa) and temperature (<70 °C). The best TOF reaches 295.4 h −1, and the Pd/CN catalyst can be used at least 6 times without obvious loss of its catalytic performance.